The Influence of Third-Party Funds, Return on Assets, and Financing to Deposit Ratio on Sharia Banking Financing In MSMEs - Rahmanisa Aulia Safitri (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2024)
This article analyzes the determinants of MSME financing at Islamic Commercial Banks. This is measured by internal bank factors, namely Third-Party Funds, Return on Assets, and Financing to Deposit Ratio. The data used is time series data sourced from the Financial Services Authority for the period January 2021 - December 2023. Through multiple linear regression analysis with the Ordinary Least Square (OLS) method, it can be concluded that: First, partially, the TPF and FDR variables have a significant positive effect on MSME Financing, while the ROA variable has an insignificant negative effect on MSME Financing for Islamic Commercial Banks. Second, simultaneously, TPF, ROA, and FDR have a significant positive effect on MSME Financing for Islamic Commercial Banks. With these results, it is hoped that this research can contribute to policy or decision making for Islamic Commercial Banks to increase financing to the MSME sector, both working capital financing and investment financing for the MSME sector in Indonesia.